Towards electronic journals: realities for scientists, librarians, and publishers, de Carol Tenopir e Donald W. King - Mueller, Suzana P. Machado (Revista de Biblioteconomia de Brasília, 2001)
TENOPIR, Carol; KING, Donald W. Towards electronic journals: realities for scientists, librarians, and publishers. Washington, DC: Special Libraries Association, 2000. xxii + 488 p.